Genetic divergence in landraces of common bean (Phaseolus vulgaris L.) from the Nilgiris - Priya, S.; Jose, Franklin Charles (The Indian Journal of Genetics and Plant Breeding, 2016)
Genetic diversity of common bean (Phaseolus vulgaris L.) was assessed based on morphological traits and RAPD markers. The principal component analysis identified eight components with eigenvalue above 1.0 and together explained 84.35% of the total variation. RAPD based dendrogram showed two major groups corresponding to the Andean and Mesoamerican gene pools. These bean landraces retain a considerable level of heterogeneity. Our results suggest that a deep knowledge of germplasm is the best strategy for preserving the diversity of common bean available with tribal farmers in remote villages of Nilgiri hills.